Murine Models of Acute Leukemia: Important Tools in Current Pediatric Leukemia Research - Jacoby, Elad; Chien, Christopher D.; Fry, Terry J. (Frontiers in Oncology, 2014)
Leukemia remains the most common diagnosis in pediatric oncology and, despite dramatic progress in upfront therapy, is also the most common cause of cancer-related death in children. Much of the initial improvement in outcomes for acute lymphoblastic leukemia (ALL) was due identification of cytotoxic agents that are active against leukemias followed by the recognition that combination of these cytotoxic agents and prolonged therapy are essential for cure. Recent data demonstrating lack of progress in patients for whom standard chemotherapy fails suggests that the ability to improve outcome for these children will not be dramatically impacted through more intensive or newer cytotoxic agents. Thus, much of the recent research focus has been in the area of improving our understanding of the genetics and the biology of leukemias. Although in vitro studies remain critical, given the complexity of a living system and the increasing recognition of the contribution of leukemia extrinsic factors such as the bone marrow microenvironment, in vivo models have provided important insights. The murine systems that are used can be broadly categorized into syngenic models in which a murine leukemia can be studied in an immunologically intact host and xenograft models where human human leukemias are studied in highly immunocompormised murine host. Both of these systems have limitations such that neither can be used exclusively to study all aspects of leukemia biology and therapeutics for humans. This review will describe the various ALL model systems that have been developed as well as discuss the advantages and disadvantages inherent to these systems that make each particularly suitable for specific types of studies.